Epidemiological as well as Microbiological Profile of Suppurative Keratitis and it's Outcome: A Prospective Hospital Based Study from Eastern Nepal - Patel, S; Badhu, BP; Khanal, B; Arya, SK (Journal of Universal College of Medical Sciences, 2013)
INTRODUCTION: Suppurative keratitis is the second most common cause of monocular blindness after unoperated cataract in some tropical developing countries. The etiological and epidemiological pattern of suppurative keratitis varies significantly with geographical region, patient's population, health of the cornea. The present study was carried out to explore the epidemiological pattern, microbiological profile and treatment outcome of suppurative keratitis at a tertiary care center in Eastern Nepal. MATERIAL AND METHODS: It was a prospective cohort study carried out in patients presented with suppurative keratitis from 1 November 2007 to 31 October 2008. Detailed clinical history, general physical examination and meticulous ophthalmological examination were carried out in all the subjects as per pro-forma. Corneal scraping was performed under aseptic condition. Material obtained from corneal scrapping was smeared on three separate glass slides for Gram stain, Giemsa stain and KOH wet mount. Material obtained from scraping was inoculated directly on to sheep's blood agar, chocolate agar, BHI, SDA media and sent for microbiological examination. Patients were followed up after 1 week, 2 weeks and 1 month of starting therapy. RESULTS: Sixty patients with suppurative keratitis were evaluated. 39 (65%) patients were male and 21 (35%) patients were female. Mean age of the patients was 41.53±17.86 year. Mean duration of illness was 20.23±18.62 days. History of ocular trauma was present in 35 (58.33%) patients. corneal ulcer was more often seen during summer (May-July) and winter (November-January) months. During culture, growth was seen in 33 (55%) patients. Fifteen cases (45.45%) had a pure bacterial growth, 10 (30.30%) patients had pure fungal growth and 8 (24.25%) cases had mixed bacterial and fungal growth. Staphylococcus aureus was isolated in 15 (25%) cases. Among fungi Aspergillus flavus, Aspergillus fumigatus, Fusarium were the frequent isolates, found in 4 (6.67%), 3 (5%), 3 (5%) cases. Staphylococcus aureus was found in all the cases with mixed growth. Out of 60 patients 49 (81.67%) patients achieved, good out come in form of complete healing of corneal ulcer. Poor outcome was seen in 11 (18.33%) patients. CONCLUSION: Suppurative keratitis was more commonly seen in middle aged male from rural areas, involved in agriculture related work. Staphylococcus aureus was the most common bacterial isolates. Aspergillus was the most common fungal species. With treatment majority of patients (81.67%) had good out come in form of complete healing of the corneal ulcer. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8757 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 3-10